2021
DOI: 10.1111/ojoa.12216
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Silver Production and the Site of Antas, Sardinia

Abstract: The article traces the development of Mediterranean silver production from the Iron Age to the time of Rome, focusing on the site of Antas, Sardinia. Antas is located in a rich metalliferous area, which served as a source of lead and silver beyond the regional level. The article takes data on the exploitation of metal resources as a gauge for Mediterranean developments, especially state formation and the rise in maritime connectivity. Sardinian Bronze Age chiefdoms seem not to have mined the local argentiferou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Because atmospheric circulation in the Mediterranean Basin is dominated by westerly winds (Ait Brahim et al, 2019;Azuara et al, 2020), the most probable source of Hg is the Iberian Peninsula where intense mining activities have been reported since the late Holocene period (Kassianidou and Knapp, 2005;Martinez-Cortizas et al, 1999), accounting for about half of the registered global Hg production in Europe (Hylander and Meili, 2003). Metal mining was also very active in Sardinia (Terpstra, 2021).…”
Section: Pre-and Historical Hg Depositionmentioning
confidence: 99%
“…Because atmospheric circulation in the Mediterranean Basin is dominated by westerly winds (Ait Brahim et al, 2019;Azuara et al, 2020), the most probable source of Hg is the Iberian Peninsula where intense mining activities have been reported since the late Holocene period (Kassianidou and Knapp, 2005;Martinez-Cortizas et al, 1999), accounting for about half of the registered global Hg production in Europe (Hylander and Meili, 2003). Metal mining was also very active in Sardinia (Terpstra, 2021).…”
Section: Pre-and Historical Hg Depositionmentioning
confidence: 99%
“…In this case, the General Lamarmora identified it as a Roman construction, belonging to the class of tetrastyle temples due to the presence of four columns placed in front of the pronaos, on the sides of which there were another column and two corner pillars. The finding suggested that the temple was to be an extra-urban sanctuary in the territory of the mining town of Metalla, mentioned in the Itinerarium Antonini, located between Neapolis and Sulki [1,4,40,41]. Even if the route of the Roman road indicated in the Itinerarium cannot be accurately reconstructed, the thirty Roman miles (45 km) of the Neapolis-Metalla stretch and the Metalla-Sulki stretch lead to locate Metalla at Fluminimaggiore, the municipality of the Antas site.…”
Section: Historical and Archaeological Evidencesmentioning
confidence: 99%
“…Thus, it is reasonable to assume that the temple was located along this main road. This hypothesis was supported by the analysis of the geomorphological, geological and archaeological data of the Iglesiente area, where it is known that the mining exploitation of the widespread metal ore deposits (mainly lead and silver) dates back to ancient times [1][2][3][4]. Several geological studies have revealed that in 2 of 34 the Fluminimaggiore area, in the surroundings of Antas, as well as in other areas of the Iglesiente, ore deposits containing lead and silver widely occur ( [5], and references therein).…”
Section: Introduction and Aims Of Researchmentioning
confidence: 97%
See 1 more Smart Citation